2017
DOI: 10.3390/fluids2040068
|View full text |Cite
|
Sign up to set email alerts
|

Axisymmetric Tornado Simulations with a Semi-Slip Boundary

Abstract: The structure of natural tornadoes and simulated analogs are sensitive to the lower boundary condition for friction. Three-dimensional numerical simulations of storms require a choice for turbulence parameterizations and resolution of wind near the lower boundary. This article explores some of the consequences of choices of a surface drag coefficient on the structure of a mature simulated tornado, using a conventional axisymmetric model. The surface drag parameterization is explored over the range of the semi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Some studies have also noted that tornado development in supercells may be impacted by elevation changes [18][19][20][21][22] while others have explored the link between tornado formation and variations in surface roughness [22][23][24]. Numerical simulations have also shown that the development of near-ground rotation is sensitive to surface friction magnitude [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also noted that tornado development in supercells may be impacted by elevation changes [18][19][20][21][22] while others have explored the link between tornado formation and variations in surface roughness [22][23][24]. Numerical simulations have also shown that the development of near-ground rotation is sensitive to surface friction magnitude [25][26][27].…”
Section: Introductionmentioning
confidence: 99%